Reverse genetic analysis of gene Pp1s148_40v6 in Physcomitrella patens : an AtMAX2 orthologue? - De Villiers, Ruan Morne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.